SARS-CoV-2 Mutations and Their Impact on Diagnostics, Therapeutics and Vaccines - Thakur, Suresh; Sasi, Shalitha; Pillai, Sindhu Gopinathan; Nag, Ayantika; Shukla, Dhananjay; Singhal, Ritu; Phalke, Sameer; Velu, G. S. K. (Frontiers in Medicine, 2022)
With the high rate of COVID-19 infections worldwide, the emergence of SARS-CoV-2 variants was inevitable. Several mutations have been identified in the SARS-CoV-2 genome, with the spike protein as one of the mutational hot spots. Specific amino acid substitutions such as D614G and N501Y were found to alter the transmissibility and virulence of the virus. The WHO has classified the variants identified with fitness-enhancing mutations as variants of concern (VOC), variants of interest (VOI) or variants under monitoring (VUM). The VOCs pose an imminent threat as they exhibit higher transmissibility, disease severity, and ability to evade vaccine-induced and natural immunity. Here we review the mutational landscape on the SARS-CoV-2 structural and non-structural proteins and their impact on diagnostics, therapeutics and vaccines. We also look at the effectiveness of approved vaccines, antibody therapy and convalescent plasma on the currently prevalent VOCs, which are B.1.17, B.1.351, P.1, B.1.617.2 and B.1.1.529. We further discuss the possible factors influencing mutation rates and future directions.